2018
DOI: 10.1016/j.energy.2018.04.088
|View full text |Cite
|
Sign up to set email alerts
|

Performance mapping of the R744 ejectors for refrigeration and air conditioning supermarket application: A hybrid reduced-order model

Abstract: The continuous derivation of the ambient temperature and cooling demand in CO 2 refrigeration and air-conditioning systems equipped with multi-ejector modules for supermarkets requires the analysis of the fixed ejector utilisation in a very wide range of the operational envelope. Therefore, performance mapping of the four R744 ejectors installed in the multi-ejector pack was performed. The investigations of a single ejector's work were performed based on the proposed hybrid reduced-order model to predict the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…The same expression for the total ejector efficiency was presented by Elbel et al deriving by different approach as shown in Equation (5) [36]. This formula was used in many other literatures, as in [37][38][39]. It was defined as the ratio of the amount of the recovered ejector expansion work rate with maximum possible expansion work rate recovery potential.…”
Section: Ejector Efficiencymentioning
confidence: 98%
“…The same expression for the total ejector efficiency was presented by Elbel et al deriving by different approach as shown in Equation (5) [36]. This formula was used in many other literatures, as in [37][38][39]. It was defined as the ratio of the amount of the recovered ejector expansion work rate with maximum possible expansion work rate recovery potential.…”
Section: Ejector Efficiencymentioning
confidence: 98%
“…Some miscellaneous theoretical cycles of the two-phase ejector are summarized in Table 8. Recently, Haida et al [197] proposed a performance mapping of four CO 2 ejectors installed in a multi-ejector module to be integrated with supermarket refrigeration systems. The proposed model was generated by use of experimental data together with CFD model results.…”
Section: Theoretical Studiesmentioning
confidence: 99%
“…The numerical model of the ejector used in this paper is a hybrid ROM of the R744 two-phase ejector taken from the scientific work done by Haida et al [32]. The aforementioned model was developed based on a POD approximation of the CFD results and experimental data.…”
Section: A Hybrid Reduced-order Modelmentioning
confidence: 99%
“…The CFD results used to build the hybrid ROM were performed using the modified HRM [27] within the operating regime presented in Figure 2 with a defined pressure difference step of 1 bar and a temperature difference step of 5 K. Therefore, the total number of the CFD points was 5380, which were combined with approximately 200 experimental data points to generate the hybrid ROM. Then, the hybrid ROM was validated for all two-phase ejectors installed in the multi-ejector module [32]. The use of experimental data with the CFD results to generate the hybrid ROM allowed the prediction of the MFR of both nozzles with an accuracy level within ±1% at each validated point.…”
Section: A Hybrid Reduced-order Modelmentioning
confidence: 99%
See 1 more Smart Citation